Predicting the Occurrence of Postoperative Distal Junctional Kyphosis in Cervical Deformity Patients. Issue 1 (17th September 2019) - Passias, Peter G; Horn, Samantha R; Oh, Cheongeun; Lafage, Renaud; Lafage, Virginie; Smith, Justin S; Line, Breton; Protopsaltis, Themistocles S; Yagi, Mitsuru; Bortz, Cole A; Segreto, Frank A; Alas, Haddy; et al.
ABSTRACT: BACKGROUND: Distal junctional kyphosis (DJK) development after cervical deformity (CD)-corrective surgery is a growing concern for surgeons and patients. Few studies have investigated risk factors that predict the occurrence of DJK. OBJECTIVE: To predict DJK development after CD surgery using predictive modeling. METHODS: CD criteria was at least one of the following: C2-C7 Coronal/Cobb > 10°, C2-7 sagittal vertical axis (cSVA) > 4 cm, chin-brow vertical angle > 25°. DJK was defined as the development of an angle <−10° from the end of fusion construct to the second distal vertebra, and change in this angle by <−10° from baseline to postoperative. Baseline demographic, clinical, and surgical information were used to predict the occurrence of DJK using generalized linear modeling both as one overall model and as submodels using baseline demographic and clinical predictors or surgical predictors. RESULTS: One hundred seventeen CD patients were included. At any postoperative visit up to 1 yr, 23.1% of CD patients developed DJK. DJK was predicted with high accuracy using a combination of baseline demographic, clinical, and surgical factors by the following factors: preoperative neurological deficit, use of transition rod, C2-C7 lordosis (CL)<−12°, T1 slope minus CL > 31°, and cSVA > 54 mm. In the model using only baseline demographic/clinical predictors of DJK, presence of comorbidities, presence of baseline neurological deficit, and high preoperative C2-T3 angle were included in the final model (area under the curve = 87%). The final model using only surgical predictors for DJK included combined approach, posterior upper instrumented vertebrae below C4, use of transition rod, lack of anterior corpectomy, more than 3 posterior osteotomies, and performance of a 3-column osteotomy. CONCLUSION: Preoperative assessment and consideration should be given to these factors that are predictive of DJK to mitigate poor outcomes.